Food wastage awareness among foodservice undergraduates in UiTM Terengganu / Zainab Ismail and Hasyimah Hishamuddin - Ismail, Zainab; Hishamuddin, Hasyimah (2021)
Food wastage is a serious issue that occurs at all stages of the cycle, starting from the moment it develops until to the moment it reaches the user. As the population of the world increases, the amount of food waste is also cataclysmic. Lack of awareness about the effect of food wastage is causing young adults to waste more food. Young adults between these ages are mostly students. There are some students that need to consider their deal of information about food waste. This study aims to identify the perception, determine the understanding and identify the awareness of food waste effect among Foodservice Management undergraduates in UiTM Terengganu on managing food wastage. This study was conducted among 153 respondents from Foodservice Management undergraduates in UiTM Terengganu by online questionnaires. The data analysis had been made by using SPSS. As the study shows that most Foodservice Management undergraduates are aware of the issues of food waste, it is crucial that the interpretation of this matter needs to be encouraged not just in schools or universities, but also to the public. With the public getting involved, the issues of food waste can be minimized throughout the time in positive ways.